THE EFFECT OF CSR ON FINANCIAL PERFORMANCE: A STUDY OF PLANTATION COMPANIES IN INDONESIA AND MALAYSIA - RAKHMAWATI, NURUL DITA PUTRI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The study is conducted to determine the influence of CSR activities disclosure on financial performance. The research object is plantation companies listed in Indonesia Stock Exchange (IDX) and Malaysia Stock Exchange (MYX) in 2013 to 2015 through purposive sampling technique. The data are analyzed by multiple linear regression method with SPSS. The result of the analysis shows that CSR have significant effect on return on equity (ROE) but have no significant effect on the stock return.Keywords: CSR, financial performance and plantation companies